A Silicon-based MEMS Vibrating Mesh Nebulizer for Inhaled Drug Delivery. (2016) - Olszewski, Oskar Z.; MacLoughlin, Ronan; Blake, Alan; O'Neill, Mike; Mathewson, Alan; Jackson, Nathan
Abstract: This paper presents a silicon-based MEMS vibrating mesh nebulizer capable of producing micro droplets for inhaled drug delivery. The device concept, design, fabrication, and measurements are presented. The core element of the nebulizer (vibrating mesh) was fabricated using silicon process and consists of 1000 tapered micro-sized apertures. During operation the mesh vibrates at high frequency with the bending profile corresponding to the 02 resonance mode. The droplet diameter measured at the device output is 3.75 μm and a typical output rate is 0.45 ml / min.